The Influence Of Customer Service And Promotion On The Decision To Use Bank Nagari Savings Products Pasar Raya Padang Branch - Putri Utari; Ash Shadiq Egim (Yayasan Edukasi Cakrawala Nusantara, 2024)
This research aims 1). To determine the partial influence of Customer Service on the decision to save at Bank Nagari Pasar Raya Branch savings. 2). To determine the partial effect of promotions in increasing the number of customers in Bank Nagari savings products, Pasar Raya Branch 3). To determine the influence of Customer Service and simultaneous promotions on customers' decisions to deposit at Bank Nagari Pasar Raya Branch. This research uses a quantitative research method, where the sampling technique uses a total sampling technique, with a sample size of 97.The analysis technique is multiple regression analysis. The results of this research show that based on the statistical t-test, it proves that the customer service variable has a significant influence on the decision to use savings products as indicated by a significance value of 0.001 < 0.05. Based on the statistical t-test, it also proves that the promotional variable has a partially significant effect on the decision to use savings products as indicated by a significance value of 0.000<0.05. Based on the f test, customer service and promotion simultaneously influence the decision to use savings products for Bank Nagari, Pasar Raya Branch, Padang customers, which is indicated by a significance value of 0.000 < 0.05. The R Square test results show that overall the variables have an influence of 75.7% on employee performance.